Introducing the Apocrypha message, context, and significance - DeSilva, David A. 1967-; Charlesworth, James H. 1940- (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2018)
This comprehensive, up-to-date introduction to the Old Testament apocryphal books summarizes their context, message, and significance. The first edition has been very well reviewed and widely adopted. It is the most substantial introduction to the Apocrypha available and has become a standard authority on the topic. The second edition has been substantially revised and updated throughout to reflect the latest scholarship. The book includes a foreword by James H. Charlesworth. -- ‡c From publisher's description
4 Maccabees: "Noble is the contest"
Includes bibliographical references (pages 423-463) and indexes
Keywords: Bible -- Criticism, interpretation, etc -- Bible; RELIGION / Biblical Criticism & Interpretation; Einführung